The Need for Reforming the Sale of Goods Ordinance of Sri Lanka: A Comparative Analysis - R.N.K. Chandrawansa (The Open University of Sri Lanka, 2020)
This research is based on the Sale of Goods Ordinance, No. 11 of 1896 which governs the sale of goods in Sri Lanka. The Ordinance is modelled on the English Sale of Goods Ordinance of 1893. Although the English law pertaining to sale of goods has been amended to cater to the modern-day developments, the Sri Lankan Ordinance has remained the same even after a century and more. This research is carried out following the traditional black letter approach of socio-legal research. Relevant reforms to the Sri Lankan Ordinance have been identified considering the relevant case laws and current developments in the sale of goods in Sri Lanka and globally. The analysis proves that there are many deficiencies in the Sri Lankan Ordinance when compared with the law in the United Kingdom and highlights the necessity for amendments in accordance with the latest technological developments and on the requisites of the parties engaged in the sale of goods. This research proposes new reforms and illustrates how the proposed reforms will provide solutions for the perceived deficiencies. This study mainly focuses on the nature of the selling goods, geographical limits related to sale of goods and the methods that the parties use to sell the goods. Furthermore, the study focuses on the remedies introduced to the parties involved in the sale of goods.